Application of Wave Action to Enhance Oil Recovery and Remove Sediments from the Pore Space of Formation Rocks - Alfayadh, Assim Х; Kemalov, Ruslan Alimovich; Alim Feizrakhmanovich Kemalov (Journal of petroleum science and technology, 2024)
This study presents a comprehensive review combined with experimental and numerical investigations into the effectiveness of acoustic wave and high-frequency (HF) radiation exposure on oil properties and core permeability to enhance oil recovery in low-permeability reservoirs. Also, a specially designed experimental setup was developed to replicate reservoir conditions, maintaining a temperature of 40 °C and a pressure of 27.58 MPa. Core samples from a reservoir in the Republic of Tatarstan were used to simulate realistic conditions of low-permeability oil reservoirs. The experiments were conducted at an HF radiation frequency of 2 GHz and acoustic wave frequencies of 3, 4, and 5 kHz. Oil viscosity and core permeability changes were evaluated over exposure times ranging from 10 to 60 minutes. Experimental results demonstrated that combined HF and acoustic wave exposure significantly reduced oil viscosity by up to 35% and increased core permeability by up to 40%, with the most effective results achieved at an acoustic frequency of 5 kHz and the maximum exposure time. Numerical modeling in COMSOL Multiphysics was employed to complement the experimental findings, visualizing sound pressure distribution within the core and its effect on the pore structure. Ultimately, these results confirm the validity of the experimental observations and suggest that combined HF and acoustic wave exposure is a promising technology for enhancing oil recovery in low-permeability reservoirs.